1980
DOI: 10.3171/jns.1980.53.3.0323
|View full text |Cite
|
Sign up to set email alerts
|

Effect of transient ischemia on free fatty acids and phospholipids in the gerbil brain

Abstract: The effect of transient bilateral carotid occulsion on levels of free fatty acids, phospholipids, and lipid peroxides in the brain was studied in gerbils. During occulsion, both saturated and polyunsaturated free fatty acids increased strikingly to approximately 11-fold in total by 30 minutes. During recirculation, however, a selectively rapid decrement occurred in arachidonic acid, while saturated fatty acids gradually decreased to their basal levels in 180 minutes. The peroxide level, estimated by a thiobarb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
110
2
4

Year Published

1981
1981
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 330 publications
(126 citation statements)
references
References 41 publications
8
110
2
4
Order By: Relevance
“…14 (upper part) shows, this was not the ca se. These results also showed that increases in total FF A co ntent (upper panel) and in polyenoic fatty acids (lower panel) persisted for some time in the re circulation period (see also Yoshida et al ., 1980). We will return to this finding in a later paragraph.…”
Section: Effe Cts Of a Trickling Oxygen Supplysupporting
confidence: 53%
See 1 more Smart Citation
“…14 (upper part) shows, this was not the ca se. These results also showed that increases in total FF A co ntent (upper panel) and in polyenoic fatty acids (lower panel) persisted for some time in the re circulation period (see also Yoshida et al ., 1980). We will return to this finding in a later paragraph.…”
Section: Effe Cts Of a Trickling Oxygen Supplysupporting
confidence: 53%
“…13). Somewhat different results were reported by Yoshida et al (1980), who fo und that 30 min of ischemia, induced in gerbils by bilateral carotid artery ligation, signifi cantly reduced the tissue co ntent of PE, but not of Pc. However, these authors measured neither indi vidual fatty acids nor the fatty acid co mposition of PE .…”
Section: Effe Cts Of a Trickling Oxygen Supplymentioning
confidence: 59%
“…amounts, but accumulates under adverse conditions such as cerebral ischemia (Bazan, 1970;Yoshida et al, 1980;Gardiner et al, 1981;Kinouchi et al, 1990). Release of the free fatty acid is attributable to breakdown of membrane phospholipids by activa tion of phospholipases (U memura et al, 1992).…”
mentioning
confidence: 99%
“…3 Acute ischemic stroke is known to be associated with glutathione depletion and metabolism of membrane-bound arachidonic acid. [4][5][6] Under these conditions, 12-lipoxygenase has been recognized as a key pathway of arachidonic acid metabolism, which has been directly implicated in middle-cerebral artery occlusion (MCAO)-induced injury of the brain. 7,8 In this work, we report the loss of miR-29b at the infarct site after stroke by a 12-lipoxygenase-dependent mechanism.…”
Section: Introductionmentioning
confidence: 99%